PENGEMBANGAN KETRAMPILAN BAHASA ASING BAGI SISWA SMA IMMANUEL BATAM DALAM MENYONGSONG ERA REVOLUSI INDUSTRI 4.0 - Wisnu Yuwono; Johny Budiman; Denny Denny; John Christian Tedjo; Jovan Pratama; Ferdinand Jason; Sylvia Putri; Silvia Hainia; Indramawan Indramawan; Olinda Viviani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
The purpose of this community service program is to equip and increase student interest in learning English and Mandarin through providing techniques and tips that make it easier for students to learn foreign languages at SMA Immanuel Batam. The method of implementation used is conducting webinars using the Zoom application and distributing E-Books as learning materials to make it easier for students to learn the two languages. This program is implemented for one semester and the results show that students who actively participate in activities are more motivated in learning foreign languages so that their competence increases.